2022
DOI: 10.1590/fst.81721
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and determination of bioactive compounds and antioxidant activity of buckwheat seed milling fractions

Abstract: Buckwheat is a precious source of various bioactive compounds like phenolics, flavonoids, rutin, and quercetin, etc. This research work was performed to harvest the nutraceutical potential of indigenous buckwheat varieties and their milling fractions (fine flour, coarse flour, bran flour, and husk). Common buckwheat (CBW) and Tartary buckwheat (TBW) were analyzed in terms of total phenolic content (TPC), total flavonoid content (TFC), and DPPH scavenging activity. When compared to common buckwheat, Tartary buc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…However, insoluble-bound phenols are usually combined with plant cell wall polysaccharides in the form of ester bonds or covalent bonds, so it is not easy to extract them by traditional methods, resulting in the difficulty of effective utilization of these highly active substances (Wang et al, 2022b). In recent years, more and more studies have shown that the content and antioxidant activity of insoluble-bound phenols in wheat bran are higher than those of soluble polyphenols (Mazahir et al, 2022). Through the analysis of high performance liquid chromatography, most phenols were bound to wheat bran in insoluble form, and their antioxidant activity and content were higher than those in free form (Zhang et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…However, insoluble-bound phenols are usually combined with plant cell wall polysaccharides in the form of ester bonds or covalent bonds, so it is not easy to extract them by traditional methods, resulting in the difficulty of effective utilization of these highly active substances (Wang et al, 2022b). In recent years, more and more studies have shown that the content and antioxidant activity of insoluble-bound phenols in wheat bran are higher than those of soluble polyphenols (Mazahir et al, 2022). Through the analysis of high performance liquid chromatography, most phenols were bound to wheat bran in insoluble form, and their antioxidant activity and content were higher than those in free form (Zhang et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…As one of pseudocereals, buckwheat has abundant nutritional value and powerful medicinal value, and it is an ideal raw material of functional food (Mazahir et al, 2022;Ahmed et al, 2022;Cao et al, 2022). In recent years, rational diet and balanced nutrition have received more and more attention, and buckwheat food has appeared in people's lives in the forms of staple food, convenience food, leisure food, etc., a demand that is gradually increasing (Ren et al, 2018;Ren et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolics are typical phytochemicals that are widely distributed in the different parts of plants such as roots (Wang et al, 2022), stems, leaves (Mazahir et al, 2022), fruits and seeds, showing dominant antioxidant (Mitrović et al, 2021), anti-wrinkling (Byun et al, 2021) and antidiabetic activity (Shafay et al, 2021). According to their structural characteristics, phenolic phytochemicals are generally divided into two main groups such as phenolic acids and flavonoids (Vargas-Madriz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%